PENGARUH TALENT MANAGEMENT TERHADAP EMPLOYEE RETENTION DENGAN EMPLOYEE ENGAGEMENT SEBAGAI VARIABEL MEDIASI - Ratnawati, Dian Putri Dewi; Subudi, Made (E-Jurnal Manajemen; Vol 7 No 11 (2018)DO - 10.24843/EJMUNUD.2018.v07.i11.p18, 2018)
The development of an increasingly advanced era affects the business, especially the culinary field, business competition that occurs need to be balanced with the optimal utilization of company resources. Employee retention is needed as a function and competitiveness of the company. Companies need to focus on talent management and employee engagement to engage employees who can have an effect on increasing employee retention. The purpose of this study was to examine the effect of talent management on employee retention with employee engagement as a mediation variable at the employees of Sardine Restaurant Seminyak Bali. The study used the census method in determining the sample of 60 respondents, through path analysis technique. Based on the analysis results can be seen that talent management has a positive and significant influence on employee engagement. Talent management has a positive and significant influence on employee retention. Employee engagement has a positive and significant impact on employee retention. Employee engagement is able to give positive influence in mediating talent management relationship to employee retention on Sardine Restaurant Seminyak Bali employee. Keywords: talent management, employee engagement, employee retention